Interaction of Movable Conjugations Friction Surfaces under "No-wear" Rubbing Conditions - Malyshev, Vladimir N. (Recent Progress in Science and Technology Vol. 9, 2023)
Experimental studies of friction and wear processes of copper alloy-steel pairs in glycerol in the dynamic of sliding distance 70 – 2100 meters are considered in this work. X-ray studies of the surface properties changes during interaction of the triad of friction are conducted. It is shown that micro gripping and transfer of copper alloy to the steel surface and abrasive and mechanochemical wear of the antifriction alloy take place in the initial period of the copper alloy – steel pair interaction. The results of X-ray and photoelectron spectroscopy studies of composition and thickness of the protective metal-containing films on the friction surfaces of copper alloy – steel pairs are represented. It is shown that these protective films on the friction surfaces formed under “no-wear’’ rubbing conditions represent high molecular organic compounds.